Anti-neuroinflammatory Potential of Natural Products in Attenuation of Alzheimer's Disease - Shal, Bushra; Ding, Wei; Ali, Hussain; Kim, Yeong S.; Khan, Salman (Frontiers in Pharmacology, 2018)
Alzheimer’s disease (AD) is a chronic progressive neurodegenerative disorder associated with dementia and cognitive impairment most common in elderly population. Various pathophysiological mechanisms have been proposed by numerous researcher, although, exact mechanism is not yet elucidated. Several studies have been indicated that neuroinflammation associated with deposition of amyloid- beta (Aβ) in brain is a major hallmark towards the pathology of neurodegenerative diseases. So, there is a need to unravel the link of inflammatory process in neurodegeneration. Increased microglial activation, expression of cytokines, reactive oxygen species (ROS), and nuclear factor kappa B (NF-κB) participate in inflammatory process of AD. This review mainly concentrates on involvement of neuroinflammation and the molecular mechanisms adapted by various natural compounds, phytochemicals and herbal formulations in various signaling pathways involved in neuroprotection. Currently, pharmacologically active natural products, having anti-neuroinflammatory potential are being focused which makes them potential candidate to cure AD. A number of preclinical and clinical trials have been done on nutritional and botanical agents. Analysis of anti-inflammatory and neuroprotective phytochemicals such as terpenoids, phenolic derivatives, alkaloids, glycosides, and steroidal saponins displays therapeutic potential towards amelioration and prevention of devastating neurodegeneration observed in AD.